Pengaruh Globalisasi terhadap Budaya Gotong Royong di Kabupaten Bone - Muh. Zulfikar Ridha (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2022)
Gotong royong is a social activity that is action-oriented to ease each other's workload. Nowadays, the value of mutual cooperation has experienced a drastic decline after the introduction of modernization in the rural community which has an impact on the aspects of food production and agriculture. This study aims to describe the process of eroding the culture of mutual cooperation in Cabbeng Village, Dua Boccoe District, Bone Regency. This study used purposive sampling with informants :, Head of Farmer Group, Farmers ,. The type of research used is descriptive research type and the basis of case study research. The results showed that; various activities of mutual cooperation in Cabbeng Village have been eroded, one of which is rice planting. This is due to a wide imbalance in the increase in productivity of community rice fields due to the intensification of production with less human resources. As a solution, society uses technology to replace human roles. Indigenous peoples are still trying to preserve the culture of mutual cooperation which has long been practiced by the community and is claimed to have a major contribution in the development of civilization. In reality, the current of globalization is getting stronger, thus dimming these cultural values.